Comparative Study of The Effect of Supervision and Leadership on Work Discipline on Male and Women Workers in Sharia Banking Institutions in Semarang City Banks - Rauly Sijabat (AL-ARBAH: Journal of Islamic Finance and Banking, 2021)
AbstractPurpose - This study aims to examine the effect of supervision and leadership on work discipline and to determine whether or not there are differences in work discipline among male and female workers in Islamic banking institutions in Semarang City.Method - The data collection needed was done through interviews using questionnaires and analysed using a regression test approach to test the effect between variables and a comparative test to examine differences in work discipline behaviour based on gender.Result - The results of the tests carried out in this study indicate that employee work discipline can be explained by supervision and leadership. This study also shows that there are no differences in work discipline for male and female employees who work in Islamic banking institutions in Semarang City.Implication - There is no difference in work discipline for male and female employees, so to improve work discipline, it is done by increasing supervision and leadership that applies fairly and equitably to male and female employees.Originality- Variables developed to explain work discipline behavior based on the results of previous research and have relevance to empirical phenomena. This study was also conducted a comparative study of work discipline behavior based on gender which had never been done in previous research.